2023
DOI: 10.1002/advs.202303664
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Delivery of Functional Mitochondria Rescues the Dysfunction of CD4+ T Cells in Aging

Colwyn A. Headley,
Shalini Gautam,
Angelica Olmo‐Fontanez
et al.

Abstract: Mitochondrial dysfunction alters cellular metabolism, increases tissue oxidative stress, and may be principal to the dysregulated signaling and function of CD4+ T lymphocytes in the elderly. In this proof of principle study, it is investigated whether the transfer of functional mitochondria into CD4+ T cells that are isolated from old mice (aged CD4+ T cells), can abrogate aging‐associated mitochondrial dysfunction, and improve the aged CD4+ T cell functionality. The results show that the delivery of exogenous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 134 publications
3
8
0
Order By: Relevance
“…Additionally, mito-transferred aged CD4 + T cells showed improvement in activation-induced TCR-signaling kinetics, markers of IL-2 signaling (CD25), increased IL-2 production, and enhanced proliferation ex vivo. Importantly, we showed that adoptive transfer of mito-transferred naive aged CD4 + T cells to RAG-KO mice protected them from M.tb infection [44]. These findings underscored the potential of targeted mitotransfer in rescuing aged lymphocytes, with important implications for future immunological and therapeutic studies for chronic infections and diseases [44].…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…Additionally, mito-transferred aged CD4 + T cells showed improvement in activation-induced TCR-signaling kinetics, markers of IL-2 signaling (CD25), increased IL-2 production, and enhanced proliferation ex vivo. Importantly, we showed that adoptive transfer of mito-transferred naive aged CD4 + T cells to RAG-KO mice protected them from M.tb infection [44]. These findings underscored the potential of targeted mitotransfer in rescuing aged lymphocytes, with important implications for future immunological and therapeutic studies for chronic infections and diseases [44].…”
Section: Introductionmentioning
confidence: 71%
“…Importantly, we showed that adoptive transfer of mito-transferred naive aged CD4 + T cells to RAG-KO mice protected them from M.tb infection [44]. These findings underscored the potential of targeted mitotransfer in rescuing aged lymphocytes, with important implications for future immunological and therapeutic studies for chronic infections and diseases [44].…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations